Molecular markers in the genetic diversity studies of representatives of the genus Rubus L. and prospects of their application in breeding - A. M. Kamnev; O. Yu. Antonova; S. E. Dunaeva; T. A. Gavrilenko; I. G. Chukhina (Вавиловский журнал генетики и селекции, 2020)
According to estimates of various taxonomists, the genus Rubus L. (Rosaceae Juss.) consists of 12-16 subgenera comprising ~750 species. The two largest subgenera are Idaeobatus (Focke) Focke, which includes raspberries, and the type subgenus Rubus (=Eubatus Focke), which contains blackberry species. Representatives of the genus Rubus have high nutritional and economic values, as well as medicinal properties. Breeding programs are aimed at broadening genetic diversity and creating new varieties of raspberries and blackberries that are resistant to biotic and abiotic stressors and have high fruit quality. Modern breeding and genetic programs increasingly use the achievements of molecular genetics and genomics. This paper reviews the literature data on the application of molecular markers in fundamental and applied research aimed at studying the genetic diversity of cultivated and wild species of the genus Rubus. The review describes the main types of molecular markers (RFLP, RAPD, SCoT, SSR, ISSR, AFLP, SCAR, SSCP) and their application for studying the species of the genus Rubus. The results of the work on the use of DNA markers for solving different tasks are presented, including: studying the phylogenetic relationships of species, clarifying controversial issues of taxonomy, analyzing interspecific and intraspecific diversity, genotyping and pedigree analysis of raspberry and blackberry varieties, studying somaclonal variation and others. The most important applied result is the development of molecular genetic maps for raspberry and blackberry species, on which numerous genes and QTLs conferring various valuable traits have been mapped. At the same time, the number of markers that are promising for effective molecular screening is still insufficient.